Пересадка сердца: вопросы клиники и теории / В. И. Бураковский, М. А. Фролова, Г. Э. Фальковский - Бураковский Владимир Иванович (Сабчота Сакартвело, 1977)
Экземпляры: КХ (20130130) / Инвентарный номер: 671602 / Цена: 2.70 / Сис.шифр: 617 / Авт.знак: Б 91 / ГРНТИ: 76 / ББК: 5